Benefits and Risks of Epidural Analgesia in Cardiac Surgery. Issue 3 (June 2016) - Landoni, G.; Isella, F.; Greco, M.; Zangrillo, A.; Royse, C. F.
Abstract : (Abstracted from Br J Anaesth, 115:25–32, 2015) Fear of increased risk for epidural hematoma in cardiac surgery patients has caused minimized use of epidural analgesia in cardiac surgery. However, no epidural hematomas have been reported in randomized controlled trials (RCTs) or large studies.